Realistic dynamic topography through coupling geoid and hydrodynamic models of the Baltic Sea. (1st June 2021) - Jahanmard, Vahidreza; Delpeche-Ellmann, Nicole; Ellmann, Artu
Abstract: Accurate and compatible sea level data are now more important than ever before, especially in semi-enclosed sea areas that are highly exploited and surrounded by many countries, such as the Baltic Sea. Obtaining accurate sea level data is however, not only hindered by resolution deficiencies and systematic and random errors from the various available sources (e.g. satellite altimetry (SA), tide gauges (TG), hydrodynamic models (HDM), etc.), but most importantly by variations in and insufficient knowledge of the vertical reference datums. This study demonstrates that by incorporating the geoid (equipotential surface of the earth, that represents a stable vertical datum) along with a network of tide gauges and hydrodynamic models it is possible to obtain accurate and realistic sea level data. A simplified method is developed that calculates the bias between TG and HDM and identifies an optimum time period to be utilized, given the associated accuracy required. A bias period of 0–6 h results in a standard deviation of less than 5 cm at all participating TG stations. The method is tested in the estuarine water body of the Gulf of Finland (in the eastern section of the Baltic Sea). Results show that without the bias correction, the mean dynamic topography from a westerly to easterly direction along the gulf, varied from −12.7 to −8.2 cm (a difference of 4.5 cm) whilst after bias correction the model varied from 18 cm to 25.4 cm (a difference of 7.4 cm). Both these scenarios demonstrate an increasing eastward trend. Nevertheless, a major difference in quantification exists and to a first approximation, this may vary by as much as a factor of almost 2. The analysis also intrinsically identified critical areas where drastic changes in dynamic topography occur and the associated seasons. Thus, the utilization of more stable vertical reference, such as the geoid, displays promising results, that essentially allows better quantification of more realistic parameters (e.g. sea level trends, extreme value analysis etc.). In addition, it allows identification of hydrodynamic modelling imperfections and that a coherent compatibility with other sources of sea level data (e.g. SA, Global Navigational Satellite Systems etc.) is now possible. This accuracy and conformity in sea level data are urgently required for a comprehensive understanding of climate change, marine engineering and navigation applications. Highlights: Utilization of a stable vertical reference datum such as the geoid (equipotential surface of earth) allows realistic determination of sea level heights. Synergy of tide gauge, geoid and hydrodynamic models allow estimates of a spatial and temporal bias correction. For hydrodynamic models a bias correction of 0–6 h results in an accuracy of better than 5 cm. The developed method improves mean dynamic topography by a factor of almost two. Method allows consistency and accuracy amongst various sea level sources.